Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.pcrj.2005.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Asthma management: Are GINA guidelines appropriate for daily clinical practice?

Abstract: SummaryAn international group of primary care asthma experts, as well as pulmonologists and allergists from Europe and the US, met to discuss asthma management focused on the primary care office. This paper summarizes their discussions. Accuracy of diagnosis and appropriateness of treatment is variable depending on the clinical circumstances and patient group. The value of classifying patients based on baseline or static asthma severity scores remains controversial, and asthma management decisions based on sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
4

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
8
0
4
Order By: Relevance
“…Due to the limitations of guidelines, 26,27 the difficulties encountered by physicians in adhering to them, 28 and difficulties in clinical practice in managing asthma in line with recommendations, 29 the International Primary Care Airways Group (IPAG) produced its own guidelines for primary care physicians in 2005. 30 Together with the IPCRG guidelines, 14 these provide a more practical approach than the GINA Guidelines.…”
Section: Accuracy Of Diagnosismentioning
confidence: 99%
“…Due to the limitations of guidelines, 26,27 the difficulties encountered by physicians in adhering to them, 28 and difficulties in clinical practice in managing asthma in line with recommendations, 29 the International Primary Care Airways Group (IPAG) produced its own guidelines for primary care physicians in 2005. 30 Together with the IPCRG guidelines, 14 these provide a more practical approach than the GINA Guidelines.…”
Section: Accuracy Of Diagnosismentioning
confidence: 99%
“…Ein weiterer Schwerpunkt in der vorliegenden Leitlinie ist das Konzept, die Therapie gemäß Symptomenkontrolle und patientenfokussiert zu steuern sowie Asthmaschulungsmaßnahmen zu integrieren [1, 10,11]. Da im Jahr 2006 von der selben Autorengruppe eine Empfehlung zur Behandlung der rezidivierenden obstruktiven Bronchitis und des Asthma bronchiale im Vorschulalter erstellt wurde [12,13] …”
Section: Introductionunclassified
“…Furthermore, implementation of key guideline recommendations was variable, both within and between practices. Some authors have suggested that shared patient goals may be a way of improving adherence to guidelines [8,9]. This in itself is a wonderful aim; to include patients in determining acceptable outcomes.…”
mentioning
confidence: 99%